Bacterial Profile and Antibiotic Resistance Pattern among Children with Urinary Tract Infections in Dr. Soetomo Hospital, Surabaya, Indonesia - Adhima, Fauziah; Wahyunitisari, Manik Retno; Prasetyo, Risky Vitria; Setiabudi, Rebekah Juniati (Indonesian Journal of Tropical and Infectious Disease, 2022)
Urinary tract infections (UTIs) are the most common infections in pediatric patients characterized by the growth of bacteria in the urine in significant numbers. Antibiotics remain the primary treatment of UTI in children. However, there has been an increase in antibiotic resistance to uropathogens worldwide due to their inappropriate and extensive uses. There is considerable geographical variation in the distribution of bacteria and antibiotic resistance pattern. Thus, to prevent further resistance and provide empirical antibiotic options, this study aims to determine the profile of bacteria and antibiotics resistance pattern among UTI pediatric patients in Dr. Soetomo Hospital. This study was performed by collecting data from the urine culture logbook at the Clinical Microbiology Laboratory of Dr. Soetomo Hospital in July-October 2019. The sample was UTI patients aged one day – 18 years due to bacterial infection with a colony count of   â‰¥100,000 CFU/ml. In this study, 131 patients showed significant bacterial growth dominated by males and ages one month – 2 years. UTI were caused by gram-negative bacteria (74%) and gram-positive bacteria (26%), with the most bacteria found in each group were Escherichia coli and Enterococcus faecalis. E. coli showed â‰¥70% resistance to ampicillin, cefazoline, piperacillin, tetracycline, and trimethoprim-sulfamethoxazole. Comorbidities were dominated by hydronephrosis (10.98%), chronic kidney disease (9.79%) and hydrocephalus (8.09%). In conclusion, gram-negative bacteria were the leading cause of UTI in children with E. coli as the most common uropathogen, highly resistant to ampicillin and cefazolin. Gram-positive bacteria were less frequent with varied resistance patterns. Most common comorbidity was hydronephrosis.